WHY THE SUN AND THE MOON LIVE IN THE SKY - Dayrell, Elphinstone, 1869-1917; Lent, Blair; SENSEE (California : SENSEE, 2021)
An African folktale tells how the sun and water once lived on earth as friends, but because the sun failed to build his house large enough, he and his wife, the moon, were driven into the sky when the water came to visit them.
Braille Books
This book was made for those with visual impairment.
Tactile materials
Keywords: Folklore -- Africa; Braille Books; Picture books